Preparation of astaxanthin nanodispersions using gelatin-based stabilizer systems - Anarjan, Navideh; Nehdi, Imededdine Arbi; Mohamed Sbihi, Hassen; Al-Resayes, Saud Ibrahim; Malmiri, Hoda Jafarizadeh; Tan, Chin Ping (MDPI, 2014)
The incorporation of lipophilic nutrients, such as astaxanthin (a fat soluble carotenoid) in nanodispersion systems can either increase the water solubility, stability and bioavailability or widen their applications in aqueous food and pharmaceutical formulations. In this research, gelatin and its combinations with sucrose oleate as a small molecular emulsifier, sodium caseinate (SC) as a protein and gum Arabic as a polysaccharide were used as stabilizer systems in the formation of astaxanthin nanodispersions via an emulsification-evaporation process. The results indicated that the addition of SC to gelatin in the stabilizer system could increase the chemical stability of astaxanthin nanodispersions significantly, while using a mixture of gelatin and sucrose oleate as a stabilizer led to production of nanodispersions with the smallest particle size (121.4 ± 8.6 nm). It was also shown that a combination of gelatin and gum Arabic could produce optimal astaxanthin nanodispersions in terms of physical stability (minimum polydispersity index (PDI) and maximum zeta-potential). This study demonstrated that the mixture of surface active compounds showed higher emulsifying and stabilizing functionality compared to using them individually in the preparation of astaxanthin nanodispersions.